Responsible AI Practices as a Driver of Human-Centered Innovation and Creative Sustainability - Tri Setio Utomo Suharto (bit-Tech, 2025)
This study analyzes how key ethical dimensions of Artificial Intelligence (AI) shape responsible AI usage and subsequently influence human-centered innovation and creative sustainability within Indonesia’s creative industries. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), the research collected responses from 251 practitioners across application development, gaming, graphic design, animation, music, and digital video production. The model incorporates six ethical dimensions Fairness & Non-Discrimination, Transparency, Privacy & Security, Accountability, Human Oversight, and Education & Awareness examined for their effects on Responsible AI Practice (M1) and two outcome variables: Human-Centered Innovation (Y1) and Creative Sustainability (Y2). All constructs demonstrated strong measurement quality, with high reliability and convergent validity. The strongest structural effects were observed in the paths M1 → Y1 (0.874) and Y1 → Y2 (0.846), indicating that responsible AI functions as a central mechanism linking ethical principles to innovation and sustainability outcomes. The overall model demonstrated an excellent fit, confirming the robustness of the proposed framework. Beyond statistical confirmation, the study contributes to existing research by showing that ethical AI is not merely normative but directly actionable through practical mechanisms such as human-in-the-loop supervision, periodic bias audits, transparent documentation, and improved AI literacy. These findings provide clear guidance for stakeholders practitioners, firms, and policymakers on how responsible AI can be operationalized to enhance trust, preserve human creativity, and support sustainable growth in digital creative ecosystems.